Transcriptional and epigenetic regulation of T-helper lineage specification - Tripathi, Subhash K (Immunol Rev, 2014)
Combined with TCR stimuli, extracellular cytokine signals initiate the differentiation of naive CD4(+) T cells into specialized effector T-helper (Th) and regulatory T (Treg) cell subsets. The lineage specification and commitment process occurs through the combinatorial action of multiple transcription factors (TFs) and epigenetic mechanisms that drive lineage-specific gene expression programs. In this article, we review recent studies on the transcriptional and epigenetic regulation of distinct Th cell lineages. Moreover, we review current study linking immune disease-associated single-nucleotide polymorphisms with distal regulatory elements and their potential role in the disease etiology.